2017
DOI: 10.1017/s1368980017002300
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to dietary recommendations for Swedish adults across categories of greenhouse gas emissions from food

Abstract: Objective: To explore associations between diet-related greenhouse gas emissions (GHGE), nutrient intakes and adherence to the Nordic Nutrition Recommendations among Swedish adults. Design: Diet was assessed by 4 d food records in the Swedish National Dietary Survey. GHGE was estimated by linking all foods to carbon dioxide equivalents, using data from life cycle assessment studies. Participants were categorized into quartiles of energy-adjusted GHGE and differences between GHGE groups regarding nutrient intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
7
20
1
Order By: Relevance
“…In our study, reduced dietary carbon footprint over time was associated with both more healthy and unhealthy food choices. In line with previous studies 25,[28][29][30] , our results suggest that increased consumption of unhealthy choices such as sweets and snacks correlates with lower dietary carbon footprint. This finding and the call for reduced intake of animal-based foods have raised concerns regarding the nutritional adequacy of diets mainly designed to reduce the dietary carbon footprint.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, reduced dietary carbon footprint over time was associated with both more healthy and unhealthy food choices. In line with previous studies 25,[28][29][30] , our results suggest that increased consumption of unhealthy choices such as sweets and snacks correlates with lower dietary carbon footprint. This finding and the call for reduced intake of animal-based foods have raised concerns regarding the nutritional adequacy of diets mainly designed to reduce the dietary carbon footprint.…”
Section: Discussionsupporting
confidence: 92%
“…However, exclusion of meat does not necessarily result in a decreased GHGE as the sum of such dietary modifications depends on what foods are chosen to replace the meat. For example, prepared pork has a GHGE of about 10 kg CO 2 e/kg, while the corresponding value for e.g., halloumi cheese is about 17 kg CO 2 e/kg 28 . Hence, well-informed, specific and effective changes in food choices are required to achieve a reduction in climate impact of diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacing 50% of meat consumption with legumes would reduce the climate impact of the Swedish diet by 20% [12]. For example, 1 kg of soaked and boiled legumes is responsible for 0.3 kg of CO 2 emissions, whereas 1 kg of prepared beef emits 45.9 kg CO 2 [13]. However, dietary recommendations to mitigate climate change must provide adequate nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Most of previous observational studies have shown inverse associations between diet-related GHGE and adequacy of nutrient intake [ 3 ] and overall diet quality [ 4 9 ], while a few showed positive or null associations [ 2 , 7 ]. On the other hand, a series of scenario studies have shown that modeled healthy diets meeting dietary guidelines did not always improve diet-related GHGE [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%